2008
DOI: 10.1042/bj20080622
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tryptophan derivatives with SLC6A14 (ATB0,+) reveals the potential of the transporter as a drug target for cancer chemotherapy

Abstract: ATB(0,+) [SLC6A14 (solute carrier family 6 member 14)] is an Na(+)/Cl(-)-coupled amino acid transporter whose expression is upregulated in cancer. 1-Methyltryptophan is an inducer of immune surveillance against tumour cells through its ability to inhibit indoleamine dioxygenase. In the present study, we investigated the role of ATB(0,+) in the uptake of 1-methyltryptophan as a potential mechanism for entry of this putative anticancer drug into tumour cells. These studies show that 1-methyltryptophan is a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 27 publications
8
102
0
1
Order By: Relevance
“…L-Tryptophan is not an exclusive substrate for ATB 0,+ , and it also transported by L and y + L-type amino acid transporter system but is known to have higher binding affinity to ATB 0,+ than all other amino acids (Karunakaran et al, 2008). Karunakaran et al (2008) reported the inhibitory effect of a-methyl tryptophan, which is not transported by ATB 0,+ . L-lactic acid and , and L-tryptophan was higher than retina-to-sclera transport and significantly inhibited in the presence of the inhibitor cocktail, whereas there was no effect of inhibitors on the transport of phenylacetic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-Tryptophan is not an exclusive substrate for ATB 0,+ , and it also transported by L and y + L-type amino acid transporter system but is known to have higher binding affinity to ATB 0,+ than all other amino acids (Karunakaran et al, 2008). Karunakaran et al (2008) reported the inhibitory effect of a-methyl tryptophan, which is not transported by ATB 0,+ . L-lactic acid and , and L-tryptophan was higher than retina-to-sclera transport and significantly inhibited in the presence of the inhibitor cocktail, whereas there was no effect of inhibitors on the transport of phenylacetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Phenformin and cimetidine are more potent inhibitors of OCT than metformin; however, metformin was preferred since it does not interact with efflux transporters such as MDR and MRP (Pedersen et al, 2008). L-Tryptophan is not an exclusive substrate for ATB 0,+ , and it also transported by L and y + L-type amino acid transporter system but is known to have higher binding affinity to ATB 0,+ than all other amino acids (Karunakaran et al, 2008). Karunakaran et al (2008) reported the inhibitory effect of a-methyl tryptophan, which is not transported by ATB 0,+ .…”
Section: Discussionmentioning
confidence: 99%
“…1). Pharmacologic blockade of SLC6A14 in tumor cells causes amino acid starvation, autophagy followed by apoptosis, suppression of mTOR and HIF1a signaling, and inhibition of tumor growth in vitro and in vivo (41,42). However, the upregulation of this transporter is not a common phenomenon in all cancers; for example, the transporter is not upregulated in estrogen receptor-negative breast cancer.…”
Section: Slc6a14 In Cancer and The Relevance Of Its Transport Functiomentioning
confidence: 99%
“…The transporter can concentrate substrates 1000-fold more inside cells. 25 In addition to its amino acid transport, it can also transport carnitine, D-serine, NOS (nitric oxide synthase) inhibitors, conjugated drugs, and prodrugs. This property makes it unique among amino acid transporters.…”
Section: Discussionmentioning
confidence: 99%
“…ARPE-19 cells (passages [18][19][20][21][22][23][24][25] were cultured in DMEM/F-12 containing 10% heatinactivated fetal bovine serum, 15 mM HEPES, 29 mM sodium bicarbonate, penicillin (100 units/mL), and streptomycin (100 mg/mL). Cells were maintained in 75 cm 2 tissue culture flasks at 37°C, in a humidified atmosphere of 5% CO 2 and 90% relative humidity.…”
Section: Cell Culturementioning
confidence: 99%